Bronchial artery laceration and haemothorax complicating transbronchial needle aspiration. Issue 1 (7th November 2019) - Grier, William; Kalchiem‐Dekel, Or; Jeudy, Jean; Holden, Van; Sachdeva, Ashutosh; Pickering, Edward
Abstract : A 74‐year‐old woman presented with chest pain and dyspnoea following endobronchial ultrasound (EBUS)‐guided transbronchial needle aspiration (TBNA) for presumed malignancy. Computed tomography angiography revealed a left‐sided pleural effusion with hypertrophied and tortuous bronchial arteries (BAs) with contrast blush into the left lung hilum. Tube thoracostomy and pleural fluid analysis confirmed the diagnosis of haemothorax. The mechanism of injury was determined to be BA laceration during EBUS‐TBNA and drainage led to rapid improvement in the patient's symptoms. This is the first reported case of haemothorax due to BA injury during EBUS‐TBNA. Abstract : Haemothorax following an endobronchial ultrasound‐guided guided transbronchial needle aspiration (EBUS‐TBNA) as a result of bronchial artery laceration resolved with small‐bore chest tube drainage.